Studi Eksplorasi tentang Pembelajaran Ideal bagi Generasi Z di Era Revolusi Industri 4.0 - Fitriyyah, Di'amah; Helaluddin, Helaluddin (Institut Agama Islam Negeri Kendari, 2025)
One of the challenges facing universities today is the presence of Generation Z as campus residents. Generation Z has many unique traits that they need to anticipate in order to achieve their learning goals. This study aims to examine Gen Z students' perceptions and expectations of ideal learning. This study uses a qualitative design with a phenomenological approach. There were 20 students from different campuses in Serang City, Banten Province who were selected as participants using purposive sampling technique. Data had been gathered the usage of semi-dependent interviews after which analyzed the usage of thematic evaluation techniques. The results show that Gen Z defines the ideal way of learning in the sense that: (1) learning is enjoyable and not boring, (2) from the perspective of an ideal lecturers, (3) theory and practice parity, and (4) a combination of offline and online learning. Furthermore, students in the future will (1) make the most of technology, (2) adopt hybrid learning, (3) use social media as a learning medium, and (4) apply learning to teamwork and projects.